Pengetahuan Gangguan Jiwa Dengan Sikap Keluarga Terhadap Penderita Gangguan Jiwa (Knowledge of Mental Disorders and Family Attitudes Towards People with Mental Disorders) - Asri Rahmawati; Arena Lestari; Manzahri Manzahri; Sudaryono Sudaryono (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2020)
AbstractMental health is one of the significant health problems in the world, including Indonesia. Mental disorders that occur in Indonesia are caused by a variety of biological, psychological and social factors with diversity of population, so the number of cases of mental disorders continues to increase which has an impact on increasing the country's burden and decreasing human productivity for the long term. The prevalence of mental emotional disorders indicated by symptoms of depression and anxiety for ages 15 and older reaches 14 million people or 6% of the total population of Indonesia. The problem in this study was the increasing number of ODGJ in the Sukadamai Natar Puskesmas area. The purpose of this study was to find out the relationship between knowledge about mental disorders and family attitudes towards members suffering from mental disorders. This study is quantitative research with the Cross Sectinal approach design uses primary data with family subjects with mental disorders. The population of 38 patients with mental disorders. Sampling technique with non probability sampling with total population. Data analysis using Chi square test. Were 68.4% with good knowledge and 57.9% were positive. Bivariate analysis has a relationship between knowledge with attitude (p value 0.015 value OR 8.143). Efforts to increase knowledge to the community about mental disorders through counseling, both to family members, who experience mental disorders or even special groups and activities, community based work units. AbstrakKesehatan jiwa menjadi salah satu permasalahan kesehatan yang signifikan di dunia, termasuk Indonesia. Gangguan jiwa yang terjadi di Indonesia di sebabkan berbagai faktor biologis, psikologis dan sosial dengan keanekaragaman penduduk, maka jumlah kasus gangguan jiwa terus bertambah yang berdampak pada penambahan beban negara dan penurunan produktifitas manusia untuk jangka panjang. Prevalensi gangguan mental emosional yang ditunjukan dengan gejala-gejala depresi dan kecemasan untuk usia 15 tahun keatas mencapai 14 juta orang atau 6% dari jumlah penduduk Indonesia. Permasalahan dalam penelitian ini adalah meningkatnya jumlah ODGJ di wilayah Puskesmas Sukadamai Natar. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan tentang gangguan jiwa dengan sikap keluarga terhadap anggota yang menderita gangguan jiwa. Jenis penelitian ini yaitu penelitian kuantitatif dengan rancangan pendekatan cross sectinal menggunakan data primer dengan subyek keluarga penderita gangguan jiwa. Jumlah populasi 38 penderita dengan gangguan jiwa. Tehnik pengambilan sampel dengan non probability sampling dengan total populasi. Analisa data menggunakan uji chi square. Hasil analisis menunjukkan terdapat 68,4% keluarga dengan pengetahuan baik dan 57,9% bersikap positif, analisis bivariat ada hubungan antara pengetahuan dan sikap (p value 0,015 nilai OR 8,143. Saran: upaya peningkatan pengetahuan kepada masyarakat tentang gangguan jiwa melalui penyuluhan langsung kepada anggota keluarga yang mengalami ganguan jiwa ataupun melalui kelompok-kelompok khusus dan kegiatan UKBM.